Customer Spending Pattern Analysis with Market Basket Analysis to Produce Product Strategy and Price Bundling at Kopi Soe Mekarwangi Bandung - Rachmawati, Indira; Irawan, Herry; Joshua, Anthonio (Journal Research of Social Science, Economics, and Management, 2023)
Coffee industry in Indonesia will always grow significantly. With the return of consumptions in coffee shops and take away coffee shops after the pandemic, Kopi Soe Mekarwangi Bandung as one of the players in Bandung’s coffee industries hope to experience increases in sales and profit. But what happened was the contrary, for in January 2022-January 2023, Kopi Soe Mekarwangi experienced a decline in their sales and profit. Based on the data gained from the International Coffee Organization and Toffin, coffee shops should be increasing their sales in that period. To get a deeper knowledge about the research object, an interview with the owner of Kopi Soe Mekarwangi Bandung was done and it was found that they have one fundamental marketing problem in the term of their bundle. For their bundling strategy, the basis of their decision is either (1) introducing new products, or (2) boosting slow moving products. Based on the literature and journals, it was found that the best basis for marketing strategies should be the customer spending pattern. The customer’s spending pattern can be seen in their transactions and can be analyzed using data mining techniques such as market basket analysis. It’s hoped that the result of this mining can be used to determine the best bundling strategies for Kopi Soe Mekarwangi Bandung in the future.